(untitled) - Mandelkern, Leo (Cambridge, UK, 2004)
The new edition is considerably revised to reflect developments, new questions, and problems that have arisen since the first edition appeared in 1964. The author is no recent student to the field, making this a good introduction for advanced undergraduate and graduate students. Reflecting the quantity of new material since then, the first edition is being revised into a three- volume set. In this volume, Mandelkern (emeritus, chemistry, Florida State U., Tallahassee) describes fusion of homopolymers, polymer- diluent mixtures, polymer-polymer mixtures, the fusion of copolymers, thermodynamic quantities, and fusion of cross-linked polymers.
Keywords: Crystallization,Crystalline polymers,Polymers